Pengaruh Pola Pengolahan Terhadap Efisiensi Pengolahan Tanah Menggunakan Traktor Tangan - Adi Saputra; Siti Suharyatun; Winda Rahmawati; Warji Warji (abe.fp.unila.ac.id, 2023)
It is important to choose a tillage pattern with the aim of efficiency and effectiveness. This research aims to analyze the effect of tillage patterns using hand tractors on processing work capacity, processing time efficiency and fuel requirements. The research was conducted at the BPTP Lampung Natar Experimental Garden located in Negara Ratu Village, Natar District, South Lampung Regency, Lampung Province. The research parameters observed consisted of: work capacity, processing time efficiency and fuel consumption. The research results show that the largest work capacity value is the edge pattern with an average of 0.044 ha/hour, compared to the circular continuous pattern with an average of 0.032 ha/hour and the middle pattern with an average of 0.029 ha/hour. The highest soil processing time efficiency was the circular continuous pattern at 49.86%, then the middle pattern 44.87% and the lowest was the circular continuous pattern 40.71%. The highest fuel consumption is the middle pattern at 0.55 liters/hour, then the edge pattern at 0.53 liters/hour and the circular continuous pattern at 0.45 liters/hour. Keywords: Dry Land, Fuel Consumption, Lost Time, Work Capacity of Tillage.